2022
DOI: 10.3390/microorganisms10081684
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Community-Wide Spread of Multi-Drug Resistant Escherichia coli in Young Children in Lusaka and Ndola Districts, Zambia

Abstract: Increased antimicrobial resistance (AMR) has been reported for pathogenic and commensal Escherichia coli (E. coli), hampering the treatment, and increasing the burden of infectious diarrhoeal diseases in children in developing countries. This study focused on exploring the occurrence, patterns, and possible drivers of AMR E. coli isolated from children under-five years in Zambia. A hospital-based cross-sectional study was conducted in the Lusaka and Ndola districts. Rectal swabs were collected from 565 and 455… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 71 publications
0
13
1
Order By: Relevance
“…Aworh et al also obtained similar results of resistance; 83.3, 79.2, and 77.1% to tetracycline, sulphamethoxazole/trimethoprim, and ampicillin, respectively. A recent study on AMR in young children in Lusaka and Ndola districts of Zambia showed that E. coli had highest resistance against ampicillin (78.0%), trimethoprim-sulfamethoxazole (70.4%), and tetracycline (62.8%) ( 45 ). A review by Tadesse et al on AMR in humans found that a high level of drug resistance existed to commonly prescribed antibiotics in the African continent ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aworh et al also obtained similar results of resistance; 83.3, 79.2, and 77.1% to tetracycline, sulphamethoxazole/trimethoprim, and ampicillin, respectively. A recent study on AMR in young children in Lusaka and Ndola districts of Zambia showed that E. coli had highest resistance against ampicillin (78.0%), trimethoprim-sulfamethoxazole (70.4%), and tetracycline (62.8%) ( 45 ). A review by Tadesse et al on AMR in humans found that a high level of drug resistance existed to commonly prescribed antibiotics in the African continent ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Zambia, antimicrobial-resistant E. coli have been isolated from humans, 61 , 62 broiler chickens, 63 , 64 dairy 65 and wildlife and livestock. 66 In broilers, E. coli , was observed to be resistant to tetracycline, ampicillin, cotrimoxazole and ciprofloxacin, whereas, in dairy, it was resistant to tetracycline, ampicillin, cotrimoxazole and ciprofloxacin.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli has been known to be responsible for most cases of bacteraemia in developed countries surpassing other leading bacteraemia-causing pathogens such as S. aureus 40 . Due to the high prevalence of these microorganisms and other factors, antibiotics have been frequently overused and misused for their treatment [17,[41][42][43][44] , resulting in the development of AMR among these microorganisms [45][46][47][48][49] . Consequently, infections caused by drug-resistant strains of E. coli and S. aureus are challenging to treat, thereby contributing to increased morbidity and mortality [38][39] .…”
Section: Introductionmentioning
confidence: 99%